Perceptions of voluntary consent among jail diverted veterans with co‐occurring disorders. (1st August 2017) - Trojano, Max L.; Christopher, Paul P.; Pinals, Debra A.; Harnish, Autumn; Smelson, David
Abstract : This study assessed perceptions of voluntary consent among 69 veterans who enrolled in a "jail diversion" program for co‐occurring disorders. Perceptions were measured using modified items from the MacArthur Perceived Coercion and Negative Pressure Scales. A majority reported that they "chose to" (88.4%) or "felt free to" (85.5%) enroll. Most reported having "control over" (69.6%) and "more influence than anyone else" regarding (60.9%) their participation. About half reported that enrollment was "their idea" (49.3%). Fewer reported perceptions of negative pressure, including the feeling that someone "talked them into" enrolling (24.6%), "threatened them with the maximum criminal punishment" (13.0%), "offered or promised them something" (5.8%), or "forced" them to enroll (5.8%). Nobody felt "tricked, lied to, or fooled into" participating. Total negative pressure scores were higher in those with combat experience, U  = 406.50, p  = .016. Although potentially inappropriate pressures were reported, these data suggest that the majority perceived enrollment as voluntary.